2013
DOI: 10.1007/s11418-013-0749-0
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin and formononetin from astragalus root enhance dimethylarginine dimethylaminohydrolase 2 and nitric oxide synthase expressions in Madin Darby Canine Kidney II cells

Abstract: Nitric oxide (NO) is a crucial vasodilator produced by nitric oxide synthase (NOS). Asymmetric dimethylarginine (ADMA) is an endogenous NOS inhibitor and mainly catabolized by dimethylarginine dimethylaminohydrolase (DDAH). As we reported, the antihypertensive effect of shichimotsukokato (SKT), a formula of Japanese traditional kampo medicine consisting of 7 crude drugs, in 5/6 nephrectomized rats, is mediated by the DDAH-ADMA-NO pathway. Our present study aimed to explore the effective compounds of SKT using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Furthermore, we also found that the expression of eNOS and nNOS reduced, and the expression of iNOS increased after the administration of Astragalus root extract. The neuronal NOS levels were elevated by the treatment of calycosin and formononetin, which were the active ingredients of Astragalus root [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also found that the expression of eNOS and nNOS reduced, and the expression of iNOS increased after the administration of Astragalus root extract. The neuronal NOS levels were elevated by the treatment of calycosin and formononetin, which were the active ingredients of Astragalus root [28].…”
Section: Discussionmentioning
confidence: 99%
“…Then, MTT dye solutions (Affymetrix, USA) were applied for 4 h at 37°C, followed by the addition of 150 μl DMSO (Sigma-Aldrich, USA) to dissolve the purple formazan. The ODs of the lysates were measured at 570 nm, with a reference absorbance at 630 nm [10].…”
Section: Methodsmentioning
confidence: 99%
“…The total flavonoids of A. mongholicus are the active components, which benefit cardiovascular disease attributed to the potent antioxidant activity in improving the atherosclerosis profile [96]. Isoflavones, calycosin and formononetin from the Astragalus root, could promote dimethylarginine dimethylaminohydrolase-2 protein and mRNA expressions in Madin Darby Canine Kidney (MDCK) II cells, and up regulate the neuronal nitric oxide synthase levels [97]. Astragaloside IV could prolong the action potential duration of guinea-pig ventricular myocytes, which might be explained by its inhibition of K + currents [98].…”
Section: Biological Activities Of the Astragalus Genusmentioning
confidence: 99%